Minat Belajar Siswa Dalam Pembelajaran PAI di SDN 4 Tamanwinangun Kebumen - Masitoh, Kholifatul; Arifah, Umi (IAINU Kebumen, 2025)
This research aims to describe the learning interest of fourth-grade students in Islamic Religious Education (PAI) at SD Negeri 4 Tamanwinangun Kebumen. Learning interest is a crucial factor in the success of the educational process, as students with higher interest are more likely to understand, internalize, and practice the knowledge they acquire. The study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that fourth-grade students generally show a strong interest in PAI learning. This is reflected in their regular attendance, active participation in classroom discussions, attentiveness to the teacher’s explanations, and enthusiastic involvement during lessons. Factors influencing learning interest include internal aspects, such as motivation, readiness, and emotional condition; external aspects, such as parental support, teaching methods, school environment, and peer influence; as well as learning approaches, both affective and practical. The study concludes that students’ learning interest significantly contributes to their understanding of PAI material. With strong interest, students not only gain accurate knowledge of Islamic teachings but also develop religious attitudes, tolerance, and the ability to practice Islamic values in their daily lives.